CD8+ T-Cell Signatures as Prognostic and Immunotherapy Response Predictors in Non-Small Cell Lung Cancer - Zhao, Tienan; Dhillon, Sarinder Kaur (Folia biologica, 2024)
Non-small cell lung carcinoma (NSCLC) represents the majority of lung cancer cases, comprising approximately 85 % of the total. The five-year survival rate for NSCLC patients remains discouragingly low. Recently, immunotherapy has emerged as a promising approach. Nevertheless, only a minority of patients experience considerable benefits from these treatments. This highlights the critical need for effective biomarkers that can predict both patient prognosis and response to immunotherapy. CD8+ T cells play a crucial role in cancer immunotherapy. Their presence within tumours is generally indicative of a favourable prognosis and increased efficacy of immunotherapy. This study was undertaken to identify and authenticate a novel biomarker signature based on CD8+ T-cell marker genes, to prognosticate therapeutic responses in individuals afflicted with NSCLC. This in-depth study was based on a total of 1,200 samples, which included four NSCLC specimens analysed through single-cell RNA sequencing (scRNA-seq), 1,000 NSCLC samples obtained from The Cancer Genome Atlas (TCGA) and 196 NSCLC specimens collected from the GSE37745 cohort. In patients with NSCLC, those presenting a favourable risk profile demonstrated notable elevations in specific immune cells while concurrently exhibiting reductions in other types. CD8+ T cells, with their established role in inducing apoptosis in cancer cells, have emerged as crucial predictors and modulators of treatment strategies for NSCLC patients. The combination of single-cell and bulk RNA sequencing has produced a biomarker signature, emphasizing the CD8+ T cells' crucial role in NSCLC prognosis and treatment.
Keywords: Male; nádory plic; NSCLC; Carcinoma, Non-Small-Cell Lung; Lung Neoplasms; prognóza; mužské pohlaví; CD8-Positive T-Lymphocytes; bulk RNA sequencing; immunotherapy response; Immunotherapy; prognostic signature; lidé; CD8-pozitivní T-lymfocyty; ženské pohlaví; Biomarkers, Tumor; Humans; nemalobuněčný karcinom plic; CD8+ T-cell marker genes; imunoterapie; Prognosis; single-cell; Female; lidé středního věku; nádorové biomarkery; Middle Aged